Petrology and geochronology of eclogites from the Lanterman Range, Antarctica - Di Vincenzo, G.; Palmeri, R.; Talarico, F. M.; Andriessen, P. A. M.; Ricci, C. A. (Journal of Petrology, 1997)
The mafic eclogites of the Lanterman Range are the first record of a well-preserved high-pressure assemblage from the Pacific end of the Transantarctic Mountains. They occur among pods and lenses (from <1 to similar to 30m in size) of mafic and ultramafic metamorphic rocks that constitute a narrow zone intercalated with amphibolite-facies metasediments. This zone extends along the faulted contact between the Wilson Terrane and the Bowers Terrane, in northern Victoria Land. Most of the amphibolites and retrogressed eclogites analysed have geochemical compositions that resemble transitional to E-type mid-ocean ridge basalt (MORB) and Nd isotope data indicative of differentiation from a depleted mantle source. The age of the igneous precursors is not well determined, but Sm-Nd whole-rock data indicate a Neoproterozoic age, most probably around 700-750 la. For this group of metabasites a tectonic setting of an incipient ocean basin is proposed on geological and geochemical grounds. In contract, the well-preserved eclogites are characterized by strong enrichment in more incompatible elements and pronounced negative Ta and Nb anomalies in MORE-normalized element patterns. Geochemical and Nd isotope data suggest that they are derived from a different mantle source with an enriched signature. The age of the protolith of the well-preserved eclogites, however, remains unconstrained. In the well-preserved eclogite samples the reaction textures testify to three main metamorphic stages: (Ij an eclogite facies stage, (2) a medium-pressure amphibolite facies stage, and (3) a low-pressure amphibolite facies stage. The high-pressure event occurred at temperatures of up to similar to 850 degrees C bared on garnet and omphacite thermometry and at a minimum pressure of similar to 15 kbar bared on the jadeitic content of omphacites. Internal Sm-Nd isochrons from two well-preserved eclogites are 500 +/- 5 Ma (rutile, clinopyroxene, amphibole, whole rock and garnet) and 492 +/- 3 Ma (rutile, clinopyroxene, whole rock and garnet). ...